Nitrative Stress-Related Autophagic Insufficiency Participates in Hyperhomocysteinemia-Induced Renal Aging. (27th January 2020) - Zhang, Shangyue; Zhang, Yuerong; Zhang, Xinyu; Luo, Chenghua; Cao, Yan; Ji, Dengyu; Yan, Wenjing; Xue, Ke; Chai, Jiayin; Dai, Hongyan; Wang, Wen
Abstract : The kidneys are important organs that are susceptible to aging. Hyperhomocysteinemia (HHcy) is a risk factor for nephropathy and is associated with chronic nephritis, purpuric nephritis, and nephrotic syndrome. Numerous studies have shown that elevated serum homocysteine levels can damage the kidneys; however, the underlying mechanism of HHcy on kidney damage remains unclear. In this study, we make use of a diet-induced HHcy rat model and in vitro cell culture to explore the role of autophagy in HHcy-induced renal aging and further explored the underlying mechanism. We demonstrated that HHcy led to the development of renal aging. Promoted kidney aging and autophagic insufficiency were involved in HHcy-induced renal aging. HHcy decreased the expression of transcription factor EB (TFEB), the key transcription factor of autophagy-related genes in renal tissue. Further experiments showed that nitrative stress levels were increased in the kidney of HHcy rats. Interestingly, pretreatment with the peroxynitrite (ONOO - ) scavenger FeTMPyP not only reduced the Hcy-induced nitrative stress in vitro but also partially attenuated the decrease in TFEB in both protein and mRNA levels. Moreover, our results indicated that HHcy reduced TFEB expression and inhibited TFEB-mediated autophagy activation by elevating nitrative stress. In conclusion, this study showed an important role of autophagic insufficiency in HHcy-induced renal aging, in which downregulation of TFEB plays a major role. Furthermore, downexpression of TFEB was associated with increased nitrative stress in HHcy. This study provides a novel insight into the mechanism and therapeutic strategy for renal aging.